Karakteristik Komposit Partikel Ijuk Mesh 50 Dengan Matrik Karet Terhadap Daya Serap Radiasi Sinar Gamma - Irawan, Feri; , Masyrukan, ST, MT; , Ir. Agus Hariyanto, MT (2016)
This study aimed to describe the manufacture of composite fibers bermatrik rubber particles and calculate the amount of the chemical composition of its supporters as well as find out how much absorption of the composite against gamma radiation. Composite manufacturing process begins with the preparation of materials to be used, namely: palm fiber, latex soupy with dry rubber content of 60%, ZnO, ZDEC, Ionol, sulfur. Fibers used originally from the fibers, then the fibers are made into powder particles without treatment (treatment) that could change the nature ijuknya own. Ijuk pollination process is done by milled, pulverized and blended up into powder particles. Particle fibers are then filtered by the mesh 50. Furthermore, the chemicals to be used, do dispersion first with a predetermined composition for 24 hours. After the mixing process of composite materials made on a glass and stirred for 15 minutes then pour in the mold with the dimensions specified. The next process of vulcanization by using an oven and heated at a temperature of 90o within 1 hour. Testing gamma refers to the SNI 18-6478-2000. The results show the value of the absorption of the composite to the highest gamma-ray radiation to the composite particles whose composition ijuknya fibers by 20 phr with absorption of 36.88% the second is the composition ijuknya 10 phr with absorption of 34.03%, while the value of absorption the lowest is without particle composite fibers, the absorption of 28.49%. Composite rubber composition larger fibers capable of absorbing radiation of gamma rays is greater than the composite rubber composition which fibers that little or no fibers.